The Blaming Function of Entity Criminal Liability - Buell, Samuel W. (2006)
Application of the doctrine of entity criminal liability, which had only a thin tort-like rationale at inception, now sometimes instantiates a social practice of blaming institutions. Examining that social practice can ameliorate persistent controversy over entity liability's place in the criminal law. An organization's role in its agent's bad act is often evaluated with a moral slant characteristic of judgments of criminality and with inquiry into whether the institution qua institution contributed to the agent's wrong. Legal process, by lending clarity and authority, enhances the communicative impact, in the form of reputational effects, of blaming an institution for a wrong. Reputational effects can flow through to individuals in ways that reduce probability of future wrongdoing by altering individual preferences and forcing reevaluation and reform of institutional arrangements. Blame and utility are closely connected here: the impulse to blame organizations and the beneficial effects of doing so both appear to depend on the degree of institutional influence on the agent. These insights imply that the doctrine should be tailored, unlike present law, to more fully exploit criminal law's expressive capital by selecting cases according to entity blameworthiness. Barriers to describing the phenomenon of organizational influence and culture prevent discovery of a first-best rule of institutional responsibility. A second-best step would be to enhance the existing doctrine's examination of agent mens rea, to impose fault only if the agent acted primarily with the intent to benefit the firm